Carbon fluxes and their drivers in integrated shrimp-razor clam culture systems - Chunpu Zhao; Shuonan Ma; Zhanfeng Liang; Ying Zeng; Cheng Luo; Jilin Xu (Aquaculture Reports)
Enhancing carbon sink function in marine aquaculture is among the most promising carbon capture approaches currently available. Ponds for cultivating shrimp and bivalves are the most prevalent aquaculture systems in the coastal areas of China, varying in culture modes with potentially different effects on carbon transformation and transport in these systems. However, quantification of the carbon budget, particularly greenhouse gas carbon emissions from these ponds, is limited, and the underlying driving factors remain unclear. This study aimed to investigate the carbon budget in three shrimp-razor clam culture systems. The findings indicated that feed (shrimp feed and bait-microalgae) and inflow water constituted the primary heterotopic carbon sources in aquaculture systems, comprising 70.4 %–82.4 %. Outflow water was the major component of carbon output, accounting for 35.6 %–53.3 %. Moreover, the tandem culture mode exhibited the most promising CO2 sink function culture mode, as evidenced by the net CO2 flux (–10.33 mg m–2 d–1) at the water-air interface (WAI). Furthermore, Spearman’s rank correlation and linear mixed models revealed that trophic status was the primary driver of CO2 fluxes at both the WAI and sediment-water interfaces. Salinity was presumably a contributing factor. Our findings suggest that tandem culture of shrimp and bivalves can be expected to enhance carbon fixation. Optimized culture management practices (feeding management and water exchange) and environmental regulation (e.g., trophic levels and salinity) further contribute to mitigating greenhouse gas emissions.